Business Process Management on Financial Performance - Amin Reza Nabi Zadeh; Ali Reza Nobari (Tehran University of Medical Sciences, 2021)
Background and Aim: Business process management is a comprehensive management approach that aims to align all dimensions and activities of the organization in line with customer needs and automates all processes of the organization. The aim of this study was to determine the effect of business process management on the financial performance of Tehran University of Medical Sciences. Materials and Methods: This research is an applied, descriptive and survey type and was conducted between the financial managers of Tehran University of Medical Sciences and Health Services in 2019. The research sample is 181 managers of 85 hospitals, faculties and research and development centers of the university who were selected from Cochranchr('39')s formula and targeted sampling method. Data collection was done by questionnaires, in financial performance of Hernaeus et al.(2012) and business process management questionnaire, Yarmohammadian, et al.(2012). The validity of the questionnaires was confirmed by convergent and divergent validity and Cronbachchr('39')s alpha reliability. In data analysis, 65.2% of male respondents, 55.49% had a masterchr('39')s degree or higher, 40.49% had an age of 40 years and 34.4% had more than 20 years of experience. Structural equation modeling (Smart.PLS software) was used to test the hypotheses. Results: Correlation of index structures of guidelines and treatment procedures and electronic files with mean variance(AVE) of 0.587 and 0.823 and profitability structures of medical centers, return on investment and value added 0.737, 0.755 and 0.750, Shows sufficient and high correlation. The effect of business process management on university financial performance was confirmed as the main hypothesis with a path coefficient of 0.881 and a significant value of 15.383. Also, the effect of corrections related to guidelines and treatment procedures with financial performance with a coefficient of 0.422 and a significant value of 3.702 and corrections related to electronic records of patients with a coefficient of 0.476 and a value of 4.334. Conclusion: Business process management system includes tools for modeling and analyzing data, integration programs, monitoring and optimization of activities that are effective in financial performance.